Quality Analysis of Massive High-Definition Video Streaming in Two-Tiered Embedded Camera-Sensing Systems - Joongheon Kim; Eun-Seok Ryu (International Journal of Distributed Sensor Networks)
This paper presents the quality analysis results of high-definition video streaming in two-tiered camera sensor network applications. In the camera-sensing system, multiple cameras sense visual scenes in their target fields and transmit the video streams via IEEE 802.15.3c multigigabit wireless links. However, the wireless transmission introduces interferences to the other links. This paper analyzes the capacity degradation due to the interference impacts from the camera-sensing nodes to the main aggregation link (AL), that is, the link from AL transmitter to AL receiver. For the study, IEEE 802.15.3c specific path-loss and antenna models are used for more precise evaluation. Finally, the quality analysis results are presented in terms of the number of cameras in a cell, beamwidth, the transmit power at camera sensor nodes, and the transmit power at AL nodes. With the listed factors, the analysis quantifies the actual video quality degradation in the presented camera sensing system.